Quick-charging type full-tab lithium ion battery and power utilization device
By adjusting the ratio of carbon material and silicon material in the negative electrode material of lithium-ion batteries and controlling the proportion of metal elements in the positive electrode material, the problem of insufficient thermal conductivity of lithium-ion batteries under fast charging conditions is solved, and higher thermal conductivity and safety are achieved.
Patent Information
- Application Number
- CN202411737545.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-11
AI Technical Summary
Existing lithium-ion batteries have insufficient thermal conductivity under fast charging conditions, resulting in rapid temperature rise, affecting battery performance and safety.
By adjusting the ratio of carbon material and silicon material in the negative electrode material, the thermal conductivity of the battery is improved, and the proportion of metal elements is regulated in the positive electrode material to ensure the conductivity and safety of the battery.
On the premise of ensuring battery performance, the thermal conductivity of lithium-ion batteries is significantly improved, the temperature increase speed is reduced, and the safety and service life of the battery are improved.
Smart Images

Figure BDA0005161848470000071 
Figure BDA0005161848470000081 
Figure BDA0005161848470000082
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a fast-charging full-tab lithium-ion battery and an electrical device. Background Art
[0002] The all-ear lithium-ion battery has achieved a significant reduction in resistance through the innovation of the ear structure, so it shows excellent performance in high-rate application scenarios, such as power tools. However, in order to achieve a higher energy density of the all-ear battery, more active materials need to be filled in a limited space. Therefore, the pole pieces of the battery cell have a higher surface density and greater compaction, and the use of foil is reduced. Therefore, the overall interface impedance of the battery cell is increased, and the thermal conductivity is reduced. In high-rate applications, especially fast charging, the temperature of the battery cell will rise rapidly, quickly triggering temperature protection. Therefore, how to improve the thermal conductivity of the all-ear lithium-ion battery by designing and optimizing the thermal conductivity coefficient is currently a very worthy issue to study. Summary of the invention
[0003] In order to solve the problem that existing lithium-ion batteries cannot balance battery performance and thermal conductivity, the present invention provides a fast-charging full-tab battery and an electrical device. The present invention improves the thermal conductivity of the battery while ensuring battery performance by adjusting the ratio of carbon material and silicon material in the negative electrode material of the full-tab battery. At the same time, the present invention also ensures the conductivity and safety of the battery by adjusting the mass ratio of each metal material in the positive electrode material.
[0004] The specific technical scheme of the present invention is:
[0005] First, the present invention provides a fast-charging full-ear lithium-ion battery, comprising a positive electrode sheet and a negative electrode sheet, wherein the negative electrode sheet comprises a negative electrode material, and the positive electrode sheet comprises a positive electrode material, wherein the negative electrode material comprises a carbon material and a silicon material, and the total carbon content A and the total silicon content B in the negative electrode material satisfy:
[0006] A≥81.75%;
[0007] 0<B≤18.25%.
[0008] In the above scheme, the total carbon content A in the negative electrode material is greater than 81.75%. Since various forms of carbon generally have relatively excellent thermal conductivity, a higher total carbon content helps to improve the thermal conductivity of lithium-ion batteries. At the same time, the negative electrode material also includes silicon materials. Elemental silicon and other forms of silicon are also materials that usually have ultra-high thermal conductivity. Therefore, adding a certain amount of silicon will also improve the thermal conductivity of lithium-ion batteries. Full-ear lithium-ion batteries refer to a part of the positive and negative current collectors along the height direction of the battery cell (accounting for 3%-10% of the electrode area) directly as positive and negative ears, without the need to weld additional ears on the current collector, reducing process complexity, improving manufacturing efficiency and battery conductivity.
[0009] Preferably, the positive electrode material includes metallic nickel and other metals, and the total nickel content in the positive electrode material is not less than 46%. Metallic nickel can effectively improve the conductivity of lithium-ion batteries.
[0010] Preferably, the other metals are at least two of manganese, aluminum, zirconium, tungsten, strontium, cobalt, titanium, antimony, magnesium, vanadium and iron, and the total mass of the other metals is more than 2% of the mass of the positive electrode material. By adding the above-mentioned metal elements, the conductivity of the lithium-ion battery can be improved while ensuring its safety.
[0011] Preferably, the carbon material is at least one of artificial graphite, natural graphite, hard carbon, soft carbon or mesophase carbon microspheres, and the silicon material is at least one of silicon-carbon material, silicon-oxygen particles and elemental silicon.
[0012] Preferably, the graphite orientation of the carbon material is not less than 2.0. The graphite orientation is a parameter that describes the degree of order in which graphite sheets are arranged in a graphite material. Graphite materials with a high degree of orientation generally have better conductivity and thermal stability, thereby improving the performance of lithium-ion batteries.
[0013] Preferably, the thermal conductivity η of the lithium-ion battery satisfies: 0.10≤|η|≤0.25. The thermal conductivity of the lithium-ion battery needs to be within a reasonable range. Generally speaking, a larger absolute value of the thermal conductivity indicates a better thermal conductivity. Therefore, when its absolute value is low, the thermal conductivity of the lithium-ion battery is poor, and the temperature rise rate is fast, which is not conducive to the fast charging and safety performance. When its absolute value is too large, the thermal conductivity of the lithium-ion battery will increase, but the benefits are limited. At the same time, the design of its material system and battery cell needs to make greater concessions, such as adjusting to a higher carbon content, etc., which leads to the degradation of the performance of the lithium-ion battery. Therefore, the thermal conductivity η of the lithium-ion battery can take into account both the thermal conductivity efficiency and the battery performance of the battery when satisfying: 0.10≤|η|≤0.25.
[0014] Preferably, the resistances of the positive electrode sheet and the negative electrode sheet are RC and RA respectively, and satisfy: RC+RA≤5.5×10 -2 Ωcm 2 If the resistance of the electrode is too high, the thermal conductivity of the lithium-ion battery will decrease. Therefore, adjusting the total resistance of the positive and negative electrode sheets within the above range can achieve a balance between the thermal conductivity efficiency and battery performance of the lithium-ion battery.
[0015] Preferably, the method for preparing the negative electrode sheet comprises the following steps:
[0016] (1) adding the negative electrode material, conductive agent, dispersant and binder into deionized water respectively, mixing and stirring in a homogenizer until the solid content is 30-60%, and obtaining a negative electrode slurry;
[0017] (2) applying the negative electrode slurry to at least one surface of a negative electrode current collector, baking, and roll-pressing to obtain the negative electrode sheet.
[0018] Preferably, the conductive agent is acetylene black and / or single-walled carbon nanotubes, the dispersant is carboxymethyl cellulose, and the binder is polyacrylic acid or styrene-butadiene rubber.
[0019] Preferably, the lithium-ion battery is a full-lug cylindrical lithium-ion battery.
[0020] Second, the present invention further provides an electrical device, comprising the lithium-ion battery described in any one of the first aspects, wherein the lithium-ion battery is used to supply power to the electrical device.
[0021] Compared with the prior art, the present invention has the following advantages:
[0022] (1) The present invention improves the thermal conductivity of lithium-ion batteries by introducing silicon materials with high thermal conductivity into negative electrode materials and regulating the content of silicon materials and carbon materials, while ensuring that the batteries have basic performance and safety;
[0023] (2) The present invention ensures the conductivity and safety of lithium-ion batteries by regulating the proportion of metal elements such as nickel in the positive electrode material;
[0024] (3) The present invention improves the thermal conductivity, electrical conductivity and safety of lithium-ion batteries by regulating the sum of the resistance of the positive electrode sheet and the negative electrode sheet and the graphite orientation of the carbon material;
[0025] (4) The thermal conductivity of the lithium-ion battery of the present invention is controlled within a reasonable range, and there will be no problems such as low thermal conductivity of the battery or degradation of basic battery performance due to exceeding the reasonable range. DETAILED DESCRIPTION
[0026] Examples of the present embodiment are described in detail below. The examples are only used to explain the present embodiment and are not to be construed as limiting the present embodiment.
[0027] In the description of the embodiments of the present application, it should be noted that all ranges disclosed in the present application will be understood to include any and all sub-ranges included therein. For example, the stated range "3% to 20%" should be deemed to include any and all sub-ranges as follows: it starts with a minimum value of 3% or greater and ends with a maximum value of 20% or less, for example, 4% to 19%, or 4.5% to 15%, or 12% to 13%. At the same time, all ranges disclosed in the present application are also deemed to include the endpoints of the ranges, unless otherwise explicitly stated. For example, the range "between 4 and 6" or "4 to 6" or "4-6" should generally be deemed to include endpoints 4 and 6.
[0028] In the description of this embodiment, "several" means one or more, "more" means more than two, "greater than", "less than", "exceed", etc. are understood to exclude the number itself, and "above", "below", "within", etc. are understood to include the number itself. If there is a description of "first" or "second", it is only used for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.
[0029] The present application provides a fast-charging full-ear lithium-ion battery. It is understandable that "fast-charging" does not constitute a restriction on the type of lithium-ion battery in the present application, and fast charging is only an application scenario of the technical solution of the present application. In some embodiments, the thermal conductivity η of the lithium-ion battery satisfies: 0.10≤|η|≤0.25. Specifically, the absolute value of the thermal conductivity η of the lithium-ion battery can be 0.1, 0.12, 0.2, 0.25, etc. It is understandable that the thermal conductivity of the lithium-ion battery needs to be within a reasonable range. Generally speaking, a larger absolute value of the thermal conductivity indicates its better thermal conductivity. Therefore, when its absolute value is low, the thermal conductivity of the lithium-ion battery is poor, but the heat dissipation of the battery cell is slow when the battery cell generates heat, and the temperature of the battery cell rises seriously, which is not conducive to the performance of fast charging and safety performance. When its absolute value is too large, the thermal conductivity of the battery cell will increase, but the benefits are limited. Its material system and battery cell design need to make greater concessions, such as requiring a higher carbon content, etc., which leads to the degradation of the performance of the lithium-ion battery. Therefore, the thermal conductivity η of the lithium-ion battery can take into account both the thermal conductivity and battery performance when the thermal conductivity η of the lithium-ion battery satisfies: 0.10≤|η|≤0.25.
[0030] The lithium-ion battery includes a negative electrode sheet and a positive electrode sheet. In some embodiments, the resistances of the positive electrode sheet and the negative electrode sheet are RC and RA, respectively, and satisfy: RC+RA≤5.5×10 -2 Ωcm 2It is understood that the positive electrode sheet resistance RC can be 0.025Ωcm 2 , 0.027Ωcm 2 , 0.023Ωcm 2 The negative electrode sheet resistance RA can be 0.005Ωcm 2 , 0.012Ωcm 2 , 0.003Ωcm 2 .
[0031] Next, the negative electrode sheet is introduced. The negative electrode sheet includes a negative electrode material, the negative electrode material includes a carbon material and a silicon material, and the total carbon content A and the total silicon content B in the negative electrode material satisfy: A≥81.75%, and 0<B≤18.25%.
[0032] It can be understood that A can be 82%, 82.5%, 83%, 83.45%, 88%, 90%, etc., and B can be 1%, 10%, 15%, 18%, etc. In some embodiments, B cannot be 0, which means that a certain amount of silicon needs to be added to the negative electrode material to improve the thermal conductivity of the lithium-ion battery and solve the technical problem of rapid heating of the lithium-ion battery.
[0033] In some embodiments, the carbon material is at least one of artificial graphite, natural graphite, hard carbon, soft carbon or mesophase carbon microspheres, and the silicon material is at least one of silicon-carbon material, silicon-oxygen particles, and elemental silicon. However, the present application is not limited to these materials, and the carbon material and silicon material can also be derived from other traditionally used materials, for example, the silicon material can also include silicon-containing alloys, silicon-nitrogen compounds, etc.
[0034] In some embodiments, the graphite orientation (OI) of the carbon material is not less than 2.0. It is understandable that the graphite orientation of the carbon material can be 2.0, 3.0, 4.0, 5.0, etc. The graphite orientation is a parameter that describes the degree of order of arrangement of graphite sheets in the graphite material. Graphite materials with high orientation usually have better conductivity and thermal stability, thereby improving the performance of lithium-ion batteries. The graphite orientation of the carbon material can be obtained by X-ray powder diffractometer testing. The specific operation is that the carbon material in the negative electrode sheet is separated from the binder after sintering at 600°C and 2h, and then tested according to the general rules of X-ray diffraction analysis and the lattice parameter determination method of graphite JIS K 0131-1996 and JB / T4220-2011. The peak area ratio of the 004 peak to the 110 peak in the XRD diffraction pattern is calculated as the orientation of the carbon material.
[0035] In some embodiments, the method for preparing the negative electrode sheet comprises the following steps:
[0036] (1) adding the negative electrode material, conductive agent, dispersant and binder into deionized water respectively, mixing and stirring in a homogenizer until the solid content is 30-60%, and obtaining a negative electrode slurry;
[0037] (2) applying the negative electrode slurry to at least one surface of a negative electrode current collector, baking, and roll-pressing to obtain the negative electrode sheet.
[0038] In some embodiments, the conductive agent is acetylene black and / or single-walled carbon nanotubes, the dispersant is carboxymethyl cellulose, and the binder is polyacrylic acid or styrene-butadiene rubber.
[0039] Next, the positive electrode sheet is introduced. The positive electrode sheet includes a positive electrode material. In some embodiments, the positive electrode material includes metal nickel and other metals. In some embodiments, the total nickel content in the positive electrode material is not less than 46%. It is understandable that the total nickel content in the positive electrode material can be 50%, 50.2%, 55%, 60%, etc.
[0040] In some embodiments, the other metals are at least two of manganese, aluminum, zirconium, tungsten, strontium, cobalt, titanium, antimony, magnesium, vanadium, and iron, and the total mass of the other metals is more than 2% of the mass of the positive electrode material. The above metal element content test method is generally obtained by making a CP cross section of the pole piece and then using EDS element content analysis test.
[0041] The present application also provides an electric device. In some embodiments, the electric device includes the above-mentioned lithium-ion battery, and the above-mentioned lithium-ion battery is used to power the electric device. In some embodiments, the electric device is a vehicle, a mobile phone, a portable device, a laptop computer, a ship, a spacecraft, an electric tool, etc. The embodiments of the present application do not impose any special restrictions on the above-mentioned electric device.
[0042] The present invention will be further explained with reference to the following examples.
[0043] Example 1
[0044] Embodiment 1 of the present invention provides a fast-charging full-tab lithium-ion battery, comprising a shell, a winding core loaded into the shell, and an electrolyte, wherein the winding core is formed by winding a positive electrode sheet, a separator, and a negative electrode sheet together.
[0045] (1) preparing a positive electrode sheet, including a positive electrode current collector aluminum foil and a positive electrode coating coated on both sides of the aluminum foil; wherein, calculated by weight percentage, the positive electrode coating comprises 96.5% of LiNi 0.88 Co 0.09 Al 0.03O2 (NCA88), 0.4% multi-walled carbon nanotube conductive agent, 1.6% Super-P (conductive carbon black) conductive agent and 1.5% polyvinylidene fluoride PVDF binder; the above substances are added into N-methylpyrrolidone and stirred to form a positive electrode slurry with a solid content of 60%, which is coated on the positive electrode collector to form a positive electrode sheet.
[0046] (2) A negative electrode sheet is prepared, including a negative electrode current collector copper foil and a negative electrode coating coated on both sides of the copper foil. Calculated by weight percentage, the negative electrode coating includes 91% artificial graphite, 5% silicon, 1.0% conductive agent acetylene black, 1% thickener CMC and 2% negative electrode binder polyacrylic acid.
[0047] (3) preparing an electrolyte solution by mixing ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) in a volume ratio of 1:1:1 to obtain an organic solvent, and then dissolving fully dried lithium salt LiPF6 in the mixed organic solvent to prepare an electrolyte solution with a concentration of 1 mol / L.
[0048] (4) The diaphragm includes a high-porosity dynamic diaphragm, a base film PE thickness of 9 um, a ceramic coating thickness of 1 um on both sides, and a PVDF coating thickness of 1 um. The air permeability of the diaphragm is 70-180s / 100mL.
[0049] (5) After the positive electrode sheet and the negative electrode sheet are rolled, slit and die-cut respectively, they are wound together with the separator at the same time. The positive electrode sheet, the negative electrode sheet and the separator are wound by a winding machine to form a winding core. The positive electrode tabs and the negative electrode tabs are cut and stacked on the winding core. Then, the positive bus bar and the negative bus bar are welded to the winding core respectively, and then the negative bus bar is welded to the steel shell. An insulating sheet is placed on the top of the positive bus bar, and the positive bus bar is welded to the cap to obtain a lithium-ion battery winding core body, which is loaded into the battery shell. After completing the injection, sealing and formation processes, the lithium-ion battery is obtained.
[0050] Performance Testing
[0051] Test 1: Thermal efficiency
[0052] Take a full-ear lithium-ion battery, attach a thermocouple at the center height of its outer surface, and place it in a 60°C oven at a constant temperature for more than 12 hours. After that, place it in a 25°C constant temperature oven and continuously monitor its temperature changes, collecting a temperature point every 10 seconds until the temperature drops below 30°C. At this time, calculate the rate of change y of temperature over time (minutes) at each temperature, as well as the temperature difference ΔT between each temperature and 25°C, and use ΔT as the horizontal axis and y as the vertical axis to draw a graph, fit the obtained points using the least squares method, and obtain y=ηΔT+b. When η is a negative number, it represents heat dissipation.
[0053] Test 2: Pole resistance
[0054] The cold pressed positive electrode and negative electrode are tested by 46 probe tester respectively, and the resistivity of the electrode is obtained. The test method can refer to "SJT 10314-1992 General Technical Requirements for DC Four-Probe Resistivity Tester".
[0055] Test 3: Total Carbon Content
[0056] Take a fresh full-ear lithium-ion battery, let it stand at 25°C for 4 hours, fully discharge it with a current of 0.2C or less than 1.0A, and let it stand for 30 minutes. Then disassemble it and obtain the negative electrode sheet, soak the negative electrode sheet in dimethyl carbonate for 2 hours, rinse it with dimethyl carbonate 3 times, dry it thoroughly, and bake it in a vacuum oven at 100°C for 2 hours. After cooling, scrape the active material layer and mix it thoroughly, randomly take at least 3 samples for testing with thermogravimetric equipment, and obtain the carbon content.
[0057] Example 2-12
[0058] Example 2-12 provides a lithium-ion battery, which differs from Example 1 in that the proportion of graphite added, nickel content, detected thermal conductivity, total carbon content, graphite orientation and other values in Example 2-12 are somewhat different, but are all within the scope of protection of the present application. The specific values are shown in Tables 1 and 2.
[0059] Comparative Examples 1-8
[0060] Comparative Examples 1-8 provide a lithium-ion battery, which is different from Example 1 in that the proportion of graphite added, the nickel content, the detected thermal conductivity, the total carbon content, the graphite orientation degree and other values in Comparative Examples 1-8 are different to a certain extent, and some of the values are beyond the scope of protection of the present application. The specific values are shown in Tables 1 and 2.
[0061] The parameters related to the negative electrode sheet in the above embodiments and comparative examples are shown in Table 1, and the parameters related to the positive electrode sheet are shown in Table 2.
[0062] Table 1
[0063]
[0064]
[0065] Table 2
[0066]
[0067]
[0068] Performance Testing
[0069] Test 1: Fast charging temperature rise
[0070] Take a lithium ion battery prepared according to any of the above embodiments, place it in a 25°C constant temperature box for more than 4 hours, and test it according to the following steps:
[0071] S1: Install a thermocouple at the center of the outer surface of the battery, discharge it at a constant current of 0.1C until it reaches 2.5V, and let it stand for 5 minutes;
[0072] S2: Charge the battery at a constant current of 0.2C to a cutoff of 4.2V, and at a constant voltage of 0.05C to a cutoff, and let it stand for 5 minutes;
[0073] S3: Discharge the battery at 0.2C constant current to 2.5V cutoff, and let it stand for 5 minutes, and read the battery capacity value C0 at this time;
[0074] S4: The battery is charged at a constant current of 3C to a cutoff of 4.2V, and is charged at a constant voltage to a cutoff of 0.05C, and is left to stand for 5 minutes;
[0075] S5: Read the peak temperature in S4 and subtract 25°C to obtain the temperature rise value.
[0076] Test 2: Cycle rate retention test
[0077] Take a lithium ion battery prepared according to any of the above embodiments, place it in a 25°C constant temperature box for more than 4 hours, and test it according to the following steps:
[0078] S1: Discharge the battery at a constant current of 0.1C to 2.5V cutoff, and let it stand for 5 minutes;
[0079] S2: Charge the battery at a constant current of 0.2C to a cutoff of 4.2V, and charge it at a constant voltage of 0.05C to a cutoff, and let it stand for 5 minutes;
[0080] S3: Discharge the battery at 0.2C constant current to 2.5V cutoff, and let it stand for 5 minutes;
[0081] S4: Charge the battery at 3C constant current to 4.2V, and charge at constant voltage to 0.05C cutoff, and let it stand for 5 minutes;
[0082] S5: Discharge the battery at 6C constant current until the battery reaches 2.5V, and leave it for 5 minutes. Read the capacity value C1 at this time.
[0083] S6: repeat the above steps S4 to S5 for 600 cycles;
[0084] S7: Read the discharge capacity of the 600th battery when it is discharged at a constant current of 6C to 2.5V as C600. The cycle performance of a single battery can be obtained by the ratio of the discharge capacity C600 of the 600th battery when it is discharged at a constant current of 6C to 2.5V and the discharge capacity C1 of the first battery when it is discharged at a constant current of 10C to 2.5V. The rate cycle capacity retention rate is: (C600 / C1)*100%.
[0085] Test 3: Short circuit safety test
[0086] Take the lithium ion battery prepared according to any of the above embodiments, place it in a 25°C constant temperature box for more than 4 hours, and test it according to the following steps:
[0087] S1: Discharge the battery at a constant current of 0.1C to 2.5V cutoff, and let it stand for 5 minutes;
[0088] S2: Charge the battery at a constant current of 0.2C to a cutoff of 4.2V, and charge it at a constant voltage of 0.05C to a cutoff, and let it stand for 5 minutes;
[0089] S3: Discharge the battery at 0.2C constant current to 2.5V cutoff, and let it stand for 5 minutes;
[0090] S4: Charge the battery at a constant current of 0.2C to a cutoff of 4.2V, and charge it at a constant voltage of 0.05C to a cutoff, and let it stand for 5 minutes;
[0091] S5: Use a 20mΩ resistor to short-circuit the positive and negative electrodes of the battery and record the voltage and temperature of the battery;
[0092] S6: If there is no fire during the whole process and the battery temperature is lower than 150°C, it is considered to have passed the test, otherwise it is considered to have failed;
[0093] S7: Test 5 batteries in parallel, and the percentage of batteries that pass is called the pass rate.
[0094] The test results are shown in Table 3.
[0095] Table 3
[0096]
[0097]
[0098] By comparing Examples 1-3 and Comparative Examples 1-2, it can be seen that when the absolute value of the thermal conductivity efficiency is within the scope of protection of the present application (0.10≤|η|≤0.25), the lithium-ion battery has good thermal conductivity, electrical conductivity and safety, while when the absolute value of the thermal conductivity efficiency exceeds this range, the above-mentioned performance of the lithium-ion battery is significantly reduced.
[0099] By comparing Example 1, Example 4, Example 5 and Comparative Example 3, it can be seen that when the sum of the resistance of the positive electrode sheet and the negative electrode sheet is within the protection scope of this application (RC+RA≤5.5*10 -2 Ωcm2), the thermal conductivity, electrical conductivity and safety of lithium-ion batteries are all good. However, when the sum of the resistances exceeds this range, the above performances of lithium-ion batteries decrease significantly.
[0100] By comparing Example 1, Example 6 and Comparative Example 4, it can be seen that when the graphite orientation degree (OI value) of the carbon material is within the scope of protection of the present application (OI value is not less than 2.0), the thermal conductivity, electrical conductivity and safety of the lithium ion battery are all good, and when the OI value exceeds this range, the above-mentioned performance of the lithium ion battery is significantly reduced.
[0101] By comparing Example 1, Example 7 and Comparative Example 5, it can be seen that when the graphite addition ratio in the negative electrode material is not less than 70%, the thermal conductivity, electrical conductivity and safety of the lithium ion battery are good, while when the ratio exceeds this range, the above performances of the lithium ion battery are significantly reduced.
[0102] By comparing Example 1, Example 8 and Comparative Example 6, it can be seen that when the total carbon content in the negative electrode material is within the scope to be protected by the present application (the total carbon content is not less than 81.75%), the thermal conductivity, electrical conductivity and safety of the lithium ion battery are all good, and when the total carbon content exceeds this range, the above-mentioned performance of the lithium ion battery is significantly reduced.
[0103] By comparing Example 1, Examples 9-12 and Comparative Example 7, it can be seen that when the total nickel content in the positive electrode material is within the scope to be protected by the present application (the total nickel content is not less than 46%), the thermal conductivity, electrical conductivity and safety of the lithium-ion battery are all good, and when the total nickel content exceeds this range, the above-mentioned performance of the lithium-ion battery is significantly reduced.
[0104] By comparing Example 1, Examples 9-12 and Comparative Example 8, it can be seen that when the content of other metals in the positive electrode material is within the scope of protection of the present application (the content of other metals is not less than 2%), the thermal conductivity, electrical conductivity and safety of the lithium-ion battery are all good, while when the content of other metals exceeds this range, the above-mentioned performance of the lithium-ion battery is significantly reduced.
[0105] It can be seen from Table 3 above that the temperature rise of the fast-charging lithium-ion battery of the present application in the 3C fast-charging temperature rise test is ≤43°C, the retention rate in the 3C / 6C cycle 600cls retention rate test is between 85%-95%, and the short-circuit test pass rate is ≥80%.
[0106] Although examples of the present embodiment have been shown and described, those skilled in the art will appreciate that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present embodiment, and the scope of the present embodiment is defined by the claims and their equivalents.
Claims
1. A fast-charge lithium-ion battery, characterized in that: It comprises a positive electrode sheet and a negative electrode sheet, wherein the negative electrode sheet comprises a negative electrode material, and the positive electrode sheet comprises a positive electrode material, wherein the negative electrode material comprises a carbon material and a silicon material, and the total carbon content A and the total silicon content B in the negative electrode material satisfy: A≥81.75%; 0<B≤18.25%。 2. The lithium-ion battery according to claim 1, characterized in that The positive electrode material includes metallic nickel and other metals, and the total nickel content in the positive electrode material is not less than 46%.
3. The lithium-ion battery according to claim 2, wherein the other metals are at least two of manganese, aluminum, zirconium, tungsten, strontium, cobalt, titanium, antimony, magnesium, vanadium and iron, and the total mass of the other metals is more than 2% of the mass of the positive electrode material.
4. The lithium-ion battery according to claim 1, characterized in that: The carbon material is at least one of artificial graphite, natural graphite, hard carbon, soft carbon or mesophase carbon microspheres, and the silicon material is at least one of silicon-carbon material, silicon-oxygen particles and elemental silicon.
5. The lithium ion battery according to claim 1 or 4, characterized in that: The graphite orientation degree of the carbon material is not less than 2.
0.
6. The lithium-ion battery according to claim 1, characterized in that The thermal conductivity efficiency η of the lithium ion battery satisfies: 0.10≤|η|≤0.
25.
7. The lithium-ion battery according to claim 1, characterized in that: The resistances of the positive electrode sheet and the negative electrode sheet are RC and RA respectively, and satisfy: RC+RA≤5.5×10 -2 Ωcm 2 .
8. The lithium-ion battery according to claim 1, characterized in that The method for preparing the negative electrode sheet comprises the following steps: (1) adding the negative electrode material, conductive agent, dispersant and binder into deionized water respectively, mixing and stirring in a homogenizer until the solid content is 30-60%, and obtaining a negative electrode slurry; (2) applying the negative electrode slurry to at least one surface of a negative electrode current collector, baking, and roll-pressing to obtain the negative electrode sheet.
9. The lithium-ion battery according to claim 8, characterized in that: The conductive agent is acetylene black and / or single-walled carbon nanotubes, the dispersant is carboxymethyl cellulose, and the binder is polyacrylic acid or styrene-butadiene rubber.
10. The lithium ion battery according to any one of claims 1 to 9, characterized in that: The lithium-ion battery is a full-lug cylindrical lithium-ion battery.
11. An electrical device, characterized in that: The lithium-ion battery comprises the lithium-ion battery described in any one of claims 1 to 10, wherein the lithium-ion battery is used to supply power to the electrical device.